FIRAT ÜNİVERSİTESİ SAĞLIK YÜKSEK OKULU SON SINIF ÖĞRENCİLERİNİN ANA ÇOCUK SAĞLIĞI VE AİLE PLANLAMASI KONUSUNDAKİ BİLGİ DÜZEYLERİ - AÇIK, Yasemin; POLAT, S. Aytaç (Cerrahpaşa Medical Journal, 2019)
Background and Design.- In the research conducted to determine the knowledge level of the senior students on maternal and infantile health and family planning at Fırat University Training College of health, all the senior students were intervened within the scope of the research and 90% of the senior students at the Department of Obstetrics (18/20), 100% of the senior students at the Department of Nursery (21/21) and 94.9 of the seniors students at the Department of Health Officer (17/18) were reached. The rate of the replies was 94.9% (56/59) when the whole cohort was considered together. Results.- The age mean of the students comprised in the research is 22.13 (±1.72). 8.9% of them are the graduates of The training High School of Health. When the family planning methods they knew were asked; the replies were oral contraceptives and RIA, condom, injectables, surgery sterilization, coitus interrupts and calendar method for 91.1% , 82.1%, 41.1%, 51.8%, 57.1%, 37.5% of the cohort respectively. The main reason for death in our country is haemorrhage for the 37.5% of them, toxaemia for the 26.8%, infection for the 42.9%, various vascular symptoms for the 19.6%, any systematic maternal disease for the 37.5% and risky pregnancies- such as being pregnant before the age of 18 or after the age of 35, less than 2 years period between two pregnancies and being pregnant more than 4 times- for the 41.1%. According to 92.9% of the students comprised in the research, Leopold handling should be used to determine the size of pregnancies; 2 doses of tetanus vaccination should be injected to the pregnant every other month for 60.7% of them; and for the 42.9%, a less than 11g/dl value of haemoglobin indicates anaemia at pregnancy. In Turkey, the most common problems about insufficient and unbalanced dieting of the 0-5 age group is malnutrition of protein and energy for the 85.7% of the research group, anaemia for the 71.4%, rickets for the 66.1% and tooth decays for the 53.6%. When the vaccinations that should be had between 0-24 moths which is evaluated on the routine vaccination calendar were asked to the cohort, the correct time of BCG vaccination was given by the 37.5% and 35.7% of them gave the correct answer for DBT and polio vaccinations. 58.9% of the students expressed that between the periods of 4 and 6 months, babies should have been fed only by breasting. Conclusion.- To sum up, inadequate knowledge of the students at the end of their last semester at the college is possibly due to the fact that they haven.t had public health lessons yet. Knowledge of these students. could be evaluated after an education of public health at the period of their graduation. Moreover, it is considered that the widely use of integral education system in all health-related schools giving an education at college levels and the use of active system in some of the lessons will assist the education.